ES Risks and Shareholder Voice - He, Yazhou Ellen; Kahraman, Bige; Lowry, Michelle (Review of Financial Studies, 2023)
Abstract We examine whether shareholder votes in environmental and social (ES) proposals are informative about firms’ ES risks. ES proposals are unique in that they nearly always fail. We examine whether mutual funds’ support for these failed proposals contains information about the ES risks that firms face. Higher support in failed ES proposals predicts subsequent ES incidents and the effects of these incidents on shareholder value. Examining the detailed records of fund votes, we find that agency frictions between a group of shareholders contribute to proposal failure. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online